Some points of the monitoring of flare stars using the synchronous network of remote telescopes - Romanyuk, Ya. (Кинематика и физика небесных тел, 2005)
We analyse the efficiency of observational campaigns which were carried out during seven years involving four astropoints in Ukraine, Russia, Greece, and Bulgaria. A possibility of the synchronous monitoring of stellar flares is discussed in this paper.